Mechanisms of Pulmonary Vein Reconnection After Radiofrequency Ablation of Atrial Fibrillation: The Deterministic Role of Contact Force and Interlesion Distance. (2nd April 2014) - PARK, CHAN‐IL; LEHRMANN, HEIKO; KEYL, CORNELIUS; WEBER, REINHOLD; SCHIEBELING, JOCHEN; ALLGEIER, JUERGEN; SCHURR, PATRICK; SHAH, ASHOK; NEUMANN, FRANZ‐JOSEF; ARENTZ, THOMAS; JADIDI, AMIR S.
Mechanisms of Pulmonary Vein Reconnection After Radiofrequency Ablation of Atrial Fibrillation Introduction Pulmonary vein reconnection (PVR) is an important cause of AF recurrence after ablation. With the advent of force sensing catheters, catheter–tissue contact can be determined quantitatively. Since contact force (CF) plays a major role in determining the characteristics of RF lesion, we prospectively assessed the mechanisms of PVR with regard to catheter‐contact and lesion distances in patients undergoing AF ablation. Methods and Results Forty symptomatic AF patients underwent wide circumferential PV isolation (PVI) with SmartTouch™ CF catheter. The exact locations of acute PVI and spontaneous or adenosine‐provoked PVR were annotated on CARTO. One thousand nine hundred and twenty‐six RF lesions isolated 153 PVs. PVR occurred in 35 (23%) PVs: 22 (63%) adenosine‐provoked and 13 (37%) spontaneous. CF was significantly lower at PVR versus PVI sites for RF lesions within 6 mm from these sites: mean CF 5 versus 11 g (P < 0.0001) and force–time integral (FTI) 225 versus 415 gs (P < 0.0001); 86% of PVR occurred with a mean CF < 10 g (FTI < 400 gs); and the remaining 14% occurred at ablation sites with a long interlesion distance (≥5 mm) despite mean CF ≥ 10 g. Eighty percent of PVR sites were located anteriorly. There were no significant differences in regard to arrhythmia freedom between the patients without (69%) versus with PVR (67%; P = 1.0). Conclusions Acutely durable PVI can be achieved when RF lesions are delivered with a mean CF ≥ 10 g and an interlesion distance <5 mm. The majority of PVR occur anteriorly due to inadequate CF or long interlesion distances.